Do we spontaneously form stable trustworthiness impressions from facial appearance?. [article]. - Klapper, Andre
It is widely assumed among psychologists that people spontaneously form trustworthiness impressions of newly encountered people from their facial appearance. However, most existing studies directly or indirectly induced an impression formation goal, which means that the existing empirical support for spontaneous facial trustworthiness impressions remains insufficient. In particular, it remains an open question whether trustworthiness from facial appearance is encoded in memory. Using the 'who said what' paradigm, we indirectly measured to what extent people encoded the trustworthiness of observed faces. The results of 4 studies demonstrated a reliable tendency toward trustworthiness encoding. This was shown under conditions of varying context-relevance, and salience of trustworthiness. Moreover, evidence for this tendency was obtained using both (experimentally controlled) artificial and (naturalistic varying) real faces. Taken together, these results suggest that there is a spontaneous tendency to form relatively stable trustworthiness impressions from facial appearance, which is relatively independent of the context. As such, our results further underline how widespread influences of facial trustworthiness may be in our everyday life. -- (from the authors)